(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The agriculture sector is one of the important sectors in India, around sixty percent of people depend on agriculture and it is the backbone for the Indian trademark. In this paper, we are implementing the assitive smart farming to the user, where the user can control the system by using the smartphone. The water resource is one of the vulnerable resources for farming and plant growth. In this, a soil moisture sensor is used, which is used to sense the moisture content in the soil and providing water for plants, and also in this, we are implementing the plant’s leafs disease detection using the image processing and sending that disease information to the user by using the GSM module. So that the user can turn ON the motor by sending the commands to the system. The main aim behind this project is it will helpful for the farmers to detect the various diseases in the earlier stage, saving them time and reduce human effort.